2017
DOI: 10.4067/s0717-95022017000200041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concurrent Training on Muscle Fibers of Wistar Rats Submitted to Standard and Hypercaloric Diets

Abstract: To analyze the effects of concurrent training (CT) on the muscle fibers of Wistar rats submitted to standard and hypercaloric diets. In total, 40 rats were used, divided into 4 groups: Sedentary Group (GS); Exercise Group (GE), Obese Sedentary Group (OS) and Obese Exercise Group (OE). The animals performed a CT protocol consisting of: muscle strength training and aerobic training, carried out 3 times a week for 45 days. The smallest diameter of muscle fibers (MDF) was analyzed to evaluate muscle hypertrophy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There seems to be evidence that when used 3x/week, concurrent training is capable of generating increased physical capacity, in particular, promoting muscle hypertrophy. Published studies using this training methodology demonstrated significant increases in the crosssectional area and smallest diameters of the muscle fibers of rats, both in aquatic environments and soil exercises, with normal and hypercaloric diets (Castoldi et al, 2013;Machado et al;Castoldi et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…There seems to be evidence that when used 3x/week, concurrent training is capable of generating increased physical capacity, in particular, promoting muscle hypertrophy. Published studies using this training methodology demonstrated significant increases in the crosssectional area and smallest diameters of the muscle fibers of rats, both in aquatic environments and soil exercises, with normal and hypercaloric diets (Castoldi et al, 2013;Machado et al;Castoldi et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…The literature demonstrates that physical exercise is able to attenuate the emergence and development of several diseases, especially chronic degenerative diseases [ 37 39 ]. In addition, it is observed that physically active individuals may present better levels of quality of life [ 30 ], as well as increased physical capabilities [ 11 , 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic training presents the ability to increase cellular organelles, such as mitochondria, improving the energy supply to the muscle (Castoldi et al, 2017a). In addition, other studies (Klemp et al, 2016;Ozaki et al, 2016;Schoenfeld et al, 2016) have demonstrated an anabolic effect through metabolic fatigue, in this way, the hypertrophy pathway would be triggered by this fatigue, not being dependent on the intensity/ load of the exercise (Fink et al, 2016).…”
Section: Discussionmentioning
confidence: 99%